Pemberian Beberapa Jenis Pupuk Kotoran Hewan pada Pertumbuhan Single Bud Chip Tebu (Saccharum officinarum L.) - Rumbekwan, Alexsandro Fransisko; Tuhumena, Veronica Leonora; Turot, Stanis Laus; Rumainum, Inna Martha (Politeknik Negeri Lampung, 2024)
Sugarcane plants in West Papua province, especially Manokwari Regency, have not been cultivated by the community. This can be seen from the presence of sugar cane plants in the yard that have not been cultivated. The aim of this research is to determine the type of animal manure fertilizer that has the best effect on the growth of single-bud chip sugar cane (Saccharum officinarum L.). The research used an experimental method and was designed with a completely randomized design (CRD) consisting of 3 treatments, namely M0 (soil), M1 (poultry manure fertilizer; 5:1), and M2 (goat manure fertilizer; 5:1) with a total of four replications. The research shows that poultry manure provides the best results for the growth of sugar cane plants. Treatment with poultry manure showed better plant height, number of leaves, and root length than other treatments.